THE PROBLEM DEFINITION OF SPECIFIC HEAT TRANSFER OF HEATING SYSTEMS - and (Municipal economy of cities. Series: «Economy science», 2013)
The equations for determining the specific heat capacity of the dimensionless heating device made from two heat exchangers. The method for determining the main parameters of installation and temperature environments at characteristic points of the circuit.